A Comparison of Customer Churn Vector Embedding Models with Deep Learning (AIUB Journal of Science and Engineering (AJSE), 2024)
In the telecommunication industry, Deep learning has been utilized for churn prediction. Some companies have used sophisticated deep learning techniques to predict churn, which yielded good results. However, future studies are still required to evaluate several deep learning mechanisms as only SoftMax Loss has been used so far. By comparing customer churn vector embedding models with several methods, including SoftMax Loss, Large Margin Cosine Loss, Semi-Supervised Learning, and a combination of Large Margin Cosine Loss and Semi-Supervised Learning, we continue our previous research to apply deep learning in predicting customer churn in the telecommunications industry in this paper. The use of Large Margin Cosine Loss has been proven in face recognition which can increase the discrimination between vectors embedding in different classes. Understanding how mixing unlabeled and labeled input might alter developing algorithms and learning behavior that benefit from this combination are the goals of semi-supervised learning. This approach successfully encouraged feature discrimination in customer behavior as well as improved the overall accuracy of the model. Large Margin Cosine Loss in this study achieved 83.74% of the F1 Score compared to other methods. It was further demonstrated that the produced vectors for churn prediction are discriminative by examining the cluster's similarity and the t-SNE plot.
Keywords: Cuctomer Churn; Deep Learning; Large Margin Cosine Loss; Semi Supervised Learning; Vector Embedding